Analysis of Hawaii Ironman performances in elite triathletes from 1981 to 2007 - Lepers, R. (Medicine & Science in Sports & Exercise, 2008)
Purpose: To examine the improvement in swimming (3.8 km), cycling (180 km), running (42.2 km), and overall performances at the Hawaii Ironman Triathlon of elite males and females between 1981 and 2007.